2016
DOI: 10.1080/10888691.2016.1160781
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescents’ relationships with pet dogs: Relationship continuity and associations with adjustment

Abstract: Research on human-animal interaction in children has been studied in isolation rather than integrated with core theories of children’s relationships. This study is one of the first to examine how children’s relationships with pet dogs are related to their human relationships (parent-child attachments, friendships) and to child adjustment, and to include observational assessment of children’s interactions with their pet dog. Children (9 to 11 years old, n = 99) completed questionnaires regarding relationships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…As part of a larger study (Kerns, Koehn, van Dulmen, Stuart-Parrigon, & Coifman, 2017), children were visited at their home after school or in the evenings, and parents provided consent for the child's participation. After completing assent forms, children completed several questionnaires (not part of the present report).…”
Section: Methodsmentioning
confidence: 99%
“…As part of a larger study (Kerns, Koehn, van Dulmen, Stuart-Parrigon, & Coifman, 2017), children were visited at their home after school or in the evenings, and parents provided consent for the child's participation. After completing assent forms, children completed several questionnaires (not part of the present report).…”
Section: Methodsmentioning
confidence: 99%
“…Field studies have found an interview protocol that emphasizes rapport throughout the interview facilitated communication and cooperation from children during maltreatment interviews (Ahern, Hershkowitz, Lamb, Blasbalg, & Winstanley, 2014; Hershkowitz, Lamb, Katz, & Malloy, 2015). Given the importance of dogs in the lives of many children (Kerns, van Dulmen, Parrigon, & Coifman, 2016), an important next step is to examine the effects of canine-assisted interviews on the accuracy and quantity of children’s reports.…”
Section: Discussionmentioning
confidence: 99%
“…While grounded theory largely encourages an open and fresh perspective when exploring new concepts, Strauss and Corbin encourage engagement with the literature as a means of identifying what is important to the developing concept [15]. Therefore, the literature was also consulted to determine behaviors that have been coded in related studies, including proximity and physical contact [16,17].…”
Section: Methodsmentioning
confidence: 99%